Decentralised ranging method for orthogonal frequency division multiple access systems with amplify‐and‐forward relays. Issue 9 (1st June 2014) - Jung, Young‐Ho; Cho, Sunghyun; You, Cheolwoo
Abstract : In this study, a decentralised ranging method for uplink orthogonal frequency division multiple access (OFDMA) systems with half‐duplex (HD) amplify‐and‐forward (AF) relay stations (RSs) is proposed. In the OFDMA systems with HD AF RSs, twice more resources and delays are required as ranging without RS. To reduce the required resources and delays for ranging, the authors propose a two‐phase ranging scheme based on the decentralised timing‐offset estimation at each ranging mobile station (MS). At the first phase, RS occasionally broadcasts timing reference signal, and at the second phase RS retransmits the collected ranging signals from the MSs. Then, each ranging MSs can individually estimate its own timing offset from the received signals. In the proposed ranging method, the base station does not need to send a timing‐adjustment message, and the overhead associated with ranging in the downlink resources, and computational complexity can be significantly reduced without degrading the timing‐offset‐estimation performance. Moreover, the delay associated with ranging can be maintained as same as ranging without RS.